2015
DOI: 10.1186/s12906-015-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Porophyllum ruderale leaf extract and 670-nm InGaP laser during burns repair in rats

Abstract: BackgroundIn this study, we investigated the effects of an extract of the leaves of Porophyllum ruderale and laser irradiation on the healing of burns.MethodsSeventy-two rats were divided in four groups: untreated controls, treated with laser irradiation, treated with P. ruderale and treated with both P. ruderale and laser irradiation. Burns were produced with a metal plate on the backs of the animals. Wound samples were collected for structural and morphometric analyses and to quantify the expression of TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Although several studies on laser photobiomodulation ensured the improvement of scar repair, specially secondintention wound healing, some studies compared the clinical efficacy of laser application with topical herbal medicine (Catarino et al, 2015;Jácomo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies on laser photobiomodulation ensured the improvement of scar repair, specially secondintention wound healing, some studies compared the clinical efficacy of laser application with topical herbal medicine (Catarino et al, 2015;Jácomo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Two different types of laser (670-InGaP and 830-nm GaAlAs) are used for Chiarotto et al [8] in the treatment of second-degree burns in rats and it was observed that the laser 670-nm InGaP was more effective in increasing the numbers fibroblast at the injury site. Other authors have also demonstrated the beneficial effects of low intensity laser in tissue repair using 670nm [6,23,24].…”
Section: Introductionmentioning
confidence: 95%
“…An extract of the leaves of Porophyllum ruderale and laser irradiation on the healing of burns were effective in decreasing the granulocytes during the repair process indicating a possible anti-inflammatory action of this extract of native flora [116].…”
Section: Other Plant Species Used In Wound Healingmentioning
confidence: 93%